(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background and Objective: Running has steadily gained worldwide popularity and is the primary mode of exercise for many. This, increase in activities have further observed a steady increase in the incidences of injuries. Recreational function and activities like running results in hip pain, limitation of motion or both. Iliopsoas, being the primary and the strongest hip flexor plays an important role in the maintaining integrity and strength of hip joint. Iliopsoas muscle tightness occur as a result of overuse or strain in recreational runners. The main goal of this study was to determine how the release of the iliopsoas affected recreational runners’ running speeds. Materials and methodology: 40 recreational runners were included in the study. Static release and Dynamic release was given to the patients. Pre-test assessments included the Straight Line Sprint Test (SPT), Manual Muscle Testing (MMT), Range of Motion (ROM), and Visual Analogue Scale (VAS) on rest and exercise. Result: Pain is significantly reduced during both, rest and VAS exercise. The mobility of the hip joint has significantly increased based on the ROM. There is a significant improvement on muscle strength evaluated by MMT. Conclusion: There is significant increase in running speed of recreational runners, along with significant decrease in pain,